An assessment of service quality in Esco Lifesciences (Bangladesh) Pvt. Limited - Ahmed, Kamrunnahar (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2019.